Dissociative Identity Disorder: A Comprehensive Review of Etiology, Diagnosis, Neurobiology, and Treatment - Fidyk, Monika; Bolek, Michał; Jagieła, Bartosz; Kędzia, Aleksandra; Musialska, Dominika; Minkiewicz, Magda (Quality in Sport, 2025)
Dissociative Identity Disorder (DID) is a complex and often misunderstood psychiatric condition characterized by the presence of two or more distinct identity states, memory disruptions, and episodes of dissociation. This review presents an overview of DID, focusing on its definition, symptoms, etiology, neurobiological underpinnings, diagnosis, treatment, and ongoing controversies. Current research highlights early childhood trauma as a key etiological factor, with emerging neuroimaging studies supporting the disorder’s distinct biological profile. Despite its prevalence, DID remains underdiagnosed and frequently misidentified as other psychiatric conditions, particularly borderline personality disorder or schizophrenia. The review also explores sociocultural influences, including the impact of social media on public awareness and self-diagnosis. Diagnostic challenges persist, though structured clinical interviews such as SCID-D-R offer reliable tools. Treatment is primarily based on long-term, phase-oriented psychotherapy, supported by adjunctive pharmacological strategies targeting comorbid symptoms. While debates surrounding the validity and origin of DID continue—particularly regarding the trauma model—empirical findings increasingly affirm the disorder’s legitimacy. Simulation of DID remains a concern, especially in forensic contexts, yet validated psychological and physiological assessments can aid in differential diagnosis. This review underscores the importance of continued research and clinical awareness to improve diagnosis, treatment outcomes, and public understanding of DID.